Post-harvest criteria and methods for routine screening of banana and plantain hybrids - Dadzie, B.K.; Orchad, J.E.; International Network for the Improvement of Banana and Plantain (1997)
This manual describes the key post-harvest criteria and methods/procedures for routine selection of new Musa hybrids. There are many post-harvest criteria for screening new banana, cooking banana and plantain hybrids, however the major ones include : post-harvest characteristics at harvest, fruit maturation, green-life and shelf-life, fruit ripening quality, sensory quality, cooking or boiling quality, processing quality, mechanical damage, physiological disorders and post-harvest diseases INIBAP / FHIA / NRI / ODA